Effect of variety and planting density on growth and yield of chickpea (Cicer arietinum L.) in northern Sudan - Mohammed, Abdel Rahman; Hamid, Samah; Ahmed, Sirelkhatim (Gezira Journal of Agricultural Science; Vol 11 No 2 (2013), 2013)
An experiment was conducted for two seasons (2009/10 and 2010/11) at Hudeiba Research Station Farm to study the effects of variety and planting density on growth and yield of irrigated chickpea. Two chickpea varieties, namely, Hawata (semi- erect) and FLIP-98- 55C (erect) were sown in mid November in each season at five planting densities, viz: 17, 22, 33, 44 and 66 plants/m 2 (1.7 x 10 5 , 2.2 x 10 5 , 3.3 x 10 5 , 4.4 x 10 5 and 6.6 x 10 5 plants/ha). The treatments were arranged in a randomized complete block design with three replicates. The results showed that Hawata was significantly earlier in number of days to 50 % flowering than FLIP- 98- 55C by 17 and 11 days, whereas, FLIP- 98- 55C was 17 cm and 20 cm taller with respect to the first season and 19 cm and 20 cm with respect to the second season than variety Hawata. ٌHawata highly significantly (P≤0.001) out-yielded FLIP-98- 55C by 53 % and 110 % in the first and second seasons, respectively, due to larger number of seeds and higher yield per plant than FLIP-98-55C , however , FLIP- 98- 55C gave higher 100- seed weight in both seasons than Hawata . On the other hand, planting density of 33 plants/m 2 significantly (P < 0.05) resulted in the highest seed yield of chickpea on both seasons. In conclusion, the highest seed yields were obtained by the two varieties at 33 plants/m 2 .         يعتبر محصول الحمص من المحاصيل البقولية الأساسية وغذاء هام للإنسان والحيوان في السودان. عليه تم إجراء تجربة خلال موسمي 2009\10 –\2010\11 في محطة بحوث الحديبة التي تقع في شمال السودان في المناخ  شبه الصحراوي. وذلك بغرض دراسة تأثير الصنف والكثافة النباتية في نمو وإنتاج الحمص المروي. استخدم الصنف حواته (شبه قائم) والصنف (فلب–FLIP-89 55C ) قائم (مستجلب من المركز الدولي لبحوث المناطق الجافة  (ICARDA) وزرع الصنفين باستخدام خمسة معاملات من الكثافة النباتية (17، 22، 33،  44 و66 نبات/ متر 2 ) والتي تعادل (170000، 220000،0، 330000، 440000 و660000 نبات/هكتار). أُستخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات. أوضحت النتائج تأثير عالي المعنوية للصنف ومعنوي للكثافة النباتية والتفاعل بين الصنف والكثافة في كلا الموسمين. الصنف حواتة مبكر في الإزهار بحوالي 17 و11 يوم في الموسم الأول والثاني علي التوالي بينما الصنف فلب تميز بالطول ب 17 و20 سم عن حواتة و10 و20 سم ارتفاع القرن الأول من سطح التربة عن حواتة. ومن ناحية أخري كان تأثير الكثافة النباتية ثابت ولكنه معنوي في 50% من عدد أيام الأزهار وطول النبات في الموسم الثاني فقط. أعطى الصنف حواته عدد أعلي من البذور للنبات في الموسمين وإنتاجية النبات الواحد في الموسم الثاني فقط عن الصنف فلب والذي تفوق عليه في وزن المائة حبة في كلا الموسمين. أوضحت النتائج أن عدد الحبوب بالنبات وإنتاجية النبات الواحد نقصت بزيادة الكثافة النباتية. كما أوضحت النتائج تفوق الصنف حواتة (3807 و3315 كجم/هكتار) عن الصنف فلب بسبة 53 و110 % في الموسم الأول والثاني علي التوالي، بينما زيادة الكثافة النباتية من 17 نبات إلي 33 نبات في المتر المربع أدي لزيادة معنوية في إنتاج بذور الحمص في كلا الموسمين (3429 و3050 كجم/هكتار). بلغت الإنتاجية أعلي قيمة لها في الكثافة النباتية 33 نبات في المتر المربع في كلا الموسمين وبذا نوصي بزراعة الحمص علي مسافة  60 و 10 سم في السراب والحفر علي التوالي أي ما يعادل 25 كجم بذور/ فدان.